Mechanism of ethanol electrooxidation on mesoporous Pt electrode in acidic medium studied by a novel electrochemical mass spectrometry set-up - Flórez Montaño, Jonathan (2016)
The electrochemical behavior and mass spectrometric features for ethanol reactions on nanostructured mesoporous platinum catalysts (MPPt) in 0.5 M H2SO4 were studied for the first time as function of the alcohol concentration. With this purpose, cyclic voltammetry and chronoamperometry techniques were combined with a new configuration of an electrochemical mass spectrometry (EC-MS), which allows high detection sensitivity with low amount of catalysts. Accordingly, a comprehensive study of the reaction mechanism and kinetics of the ethanol oxidation on MPPt in acidic medium was carried out. The water dissociation reaction and the first ethanol dehydrogenation step are proposed to be the rate-determining step (rds) for the complete ethanol oxidation reaction and the acetaldehyde production, respectively. Furthermore, acetaldehyde, acetic acid and CO2 formation were monitored during the ethanol electrooxidation reaction and the energy conversion efficiency from ethanol to CO2 was calculated. Results indicate an increment of by-side products (acetaldehyde and acetic acid) maintaining equal CO2 formation with the rise of the alcohol concentration. Consequently, the highest energy conversion efficiency to CO2 (∼11%) was achieved at 0.6 V with the lowest alcohol concentration employed (0.01 M). Results were analyzed in terms of density and type of active surface sites, applied potential and alcohol concentration.